2018
DOI: 10.1371/journal.pone.0199871
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of medical care on the westernmost remote island, Yonaguni Island, Japan: A cross-sectional study

Abstract: Yonaguni Island is a remote and isolated westernmost island in Japan, which is the fastest aging country in the world. This study evaluated the current status of medical supply-and-demand on the island and compared these results with previous surveys carried out in rural parts of Japan. This was a retrospective cohort study conducted at the Yonaguni Municipal Clinic, the only medical facility in Yonaguni Island. The participants were patients who visited the clinic over one year, between July 2015 and June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…In contrast, studies from the U.S. and England have shown that reductions in hospitalizations are associated with high proportions of primary care physicians relative to specialists [40,41]. Each of these studies offers similar reasons as to why the utilization of academic medical centers in Japan is very high, namely the free availability and ease of access in densely populated regions as well as the tertiary care focused education and training of medical students and young doctors [21,28,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies from the U.S. and England have shown that reductions in hospitalizations are associated with high proportions of primary care physicians relative to specialists [40,41]. Each of these studies offers similar reasons as to why the utilization of academic medical centers in Japan is very high, namely the free availability and ease of access in densely populated regions as well as the tertiary care focused education and training of medical students and young doctors [21,28,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of people infected with the novel coronavirus on the island continued to increase rapidly, and the family's anxiety increased because it appeared that anyone could be infected at any time. In an island where medical care is tenuous [41], older individuals are especially vulnerable to infection and their infection leads to anxiety. Thus, according to the number of infected persons, family members' emotions swung, with feelings of relief when the number of infected persons on the island was low and feelings of anxiety when the number was high.…”
Section: Positive and Negative Impacts Of Covid-19 On The Families An...mentioning
confidence: 99%